Etika Niat Abelard dan Agensi Moral dalam Pluralisme Keagamaan Indonesia - Patricius Neonnub (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2025)
This article explores Pierre Abelard’s ethics of intention (intentio and consensus) and its relevance for interfaith moral agency in contemporary Indonesia. While much of medieval ethics emphasized external law and ritual compliance, Abelard placed the moral weight on inner disposition of the will. Such a framework allows ethical recognition beyond confessional boundaries, affirming that individuals outside the Christian faith may act morally through natural law (lex naturalis). Using philosophical hermeneutics inspired by Gadamer and Ricoeur, the study engages Abelard’s Scito te ipsum, Collationes, and Commentaria in Romanos, alongside Indonesian debates on moderasi beragama and the works of Nurcholish Madjid and Yudi Latif. The findings reveal that Abelard’s emphasis on intention aligns with Indonesian concepts of civil religion and shared humanity, while also highlighting tensions with theological exclusivism. The conclusion argues that Abelard’s ethics can serve as a conceptual bridge between particular religious identities and universal values, enriching moral education, interfaith dialogue, and policy on religious moderation.